Toxicity of gold nanoparticles on somatic and reproductive cells - Taylor, U; Barchanski, A; Garrels, W; Klein, S; Kues, W; Barcikowski, S; Rath, D (Advances in experimental medicine and biology, 2012)
Along with the number of potential applications for gold nanoparticles (AuNP) especially for medical and scientific purposes, the interest in possible toxic effects of such particles is rising. The general perception views nanosized gold colloids as relatively inert towards biological systems. However, a closer analysis of pertinent studies reveals a more complex picture. While the chemical compound of which the nanoparticles consists plays an important role, further biocompatibility determining aspects have been made out. The vast majority of trials concerning AuNP-toxicity were performed using somatic cell culture lines. The results show a considerable dependency of toxic effects on size, zeta potential and surface functionalisation. In vivo studies on this subject are still rare. Based on the existing data it can be assumed, that a dosage of under <400 µg Au/kg showed no untoward effects. If higher amounts were applied toxicity depended on route of administration and particle size. Since nanoparticles have been shown to cross reproduction-relevant biological barriers such as the blood-testicle and the placental barrier the question of their reprotoxicity arises. Yet data concerning this subject is far from adequate. Regarding gametes, recent experiments showed a dose-dependent sensitivity of spermatozoa towards AuNP. Oocytes have not yet been tested in that respect. Interestingly, so far no effects were detected on embryos after gold nanoparticle exposure. In conclusion, the biocompatibility of gold nanoparticles depends on a range of particle specific aspects as well as the choice of target tissue. Further clarification of such matters are subject to ongoing research.